Pengaruh Ease Of Use dan E-Trust Terhadap Keputusan Pembelian Pada Pengguna Dompet Digital Dana Di Sidoarjo - Miranda Adityawati; Laily Muzdalifah; Ayu Lucy Larassaty; M. Mustaqim (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2022)
This research aims to 10 knowing the effect of ease of use on the purchasing decisions for Dana e-wallet users in Sidoarjo, 2) knowing the effect of e-trust on purchasing decisions for Dana e-wallet users in Sidoarjo. The research method used is a quantitative method using SPSS analysis tool to measure the result of the effect of ease of use and e-trust on purchasing decisions for Dana e-wallet users in Sidoarjo. The sample of this study amounted to 68 respondents. The place of this research was carried out in Sidoarjo Regency, especially in the Balongbendo area using the cluster sampling method. The data analys technique used is path analysis with the help of SPSS 24. Based on the result of research from the ease of use variable partially positive and significant effect on purchasing decisions. While the result variable partially has a positive and significant effect on purchasing decisions.